The treatment of migraine patients with triptans – is there a need for further Rx-to-OTC switches? - Schneider-Ziebe, Anissa; May, Uwe (Gesundheitsökonomie & Qualitätsmanagement, 2019)
Objective The disease migraine affects a large share of the German population and is linked to a high economic potential in terms of direct and indirect sickness costs. Triptans are the recommended treatment in the case of an acute migraine attack. Both, the disease and its appropriate treatment are of interest in the context of self-medication and Rx-to-OTC switch efforts. Therefore, a survey was carried out with the intention to collect data among migraine patients regarding the use of analgesics in general and of triptans specifically. This data can be the basis for further health economic considerations.Methods By an online survey among 206 migraine patients, different data regarding patients suffering from migraine, the frequency and sort of symptoms and the use of analgesics in general as well as triptans specifically was collected and analysed. A special focus was on symptoms affecting patients’ productivity, their use of triptans and their satisfaction with the current supply situation with triptans.Results The survey revealed among other findings that most patients suffer from symptoms which limit their productivity or their ability to work and make an immediate treatment necessary. Most patients know well about their disease and feel able to treat themselves in the context of self-medication once they are diagnosed by a physician. In this context a demand for further triptans available without a prescription could be identified. This is specifically, because patients respond differently to various triptans. Therefore, a larger variety of prescription free triptans would increase the number of patients with access to OTC triptans significantly.Conclusion Most survey respondents know well about their disease and the appropriate treatment and feel able to treat themselves within the scope of self-medication. Nevertheless, they mostly respond to one triptan only. In the case of an acute migraine attack an immediate treatment is required, ideal is an intake of triptans as soon as first symptoms occur. In this context pharmacies play an important role as fast and low-threshold access point to medications. Because only a limited number of patients responds to the already prescription free available triptans, there is a demand for further Rx-to-OTC switches of triptans among migraine patients which should be considered in further switch efforts in Germany.
Keywords: Migraine; Triptans; Self-medication; Rx-to-OTC switch; Germany